A double carbon-coated SnTe / CoTe2 composite material and its preparation method and application

By using double carbon coated SnTe/CoTe2 composite material in the negative electrode material of sodium ion battery, the structural stability and cycle stability problems caused by precipitation and agglomeration of Sn-based materials during heat treatment are solved, and the effects of high capacity, long cycle life and excellent rate performance are achieved.

CN116014090BActive Publication Date: 2025-04-29GUANGDONG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211591826.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-12
Publication Date
2025-04-29
Estimated Expiration
2042-12-12

AI Technical Summary

Technical Problem

In the heat treatment of the existing sodium ion battery negative electrode materials, the active material precipitation and agglomeration caused by the low melting point of Sn, resulting in poor structural stability, capacity attenuation and cycle stability.

Method used

The SnTe/CoTe2 composite is coated with dual carbon, and the carbon material is filled in the internal voids of the carbon nanofiber and the hollow core of the SnTe/CoTe2 to form a core-shell structure, fixing and limiting the active material, and preventing the Sn-based material from precipitating and agglomerating during heat treatment.

Benefits of technology

It significantly improves the structural stability of the negative electrode material, extends the cycle life, improves the capacity retention rate and rate performance, and solves the capacity reduction problem caused by the agglomeration of Sn-based materials during long-term circulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116014090B_ABST
    Figure CN116014090B_ABST
Patent Text Reader

Abstract

The present invention provides a double carbon-coated SnTe / CoTe2 composite material, a preparation method and an application thereof. The double carbon-coated SnTe / CoTe2 composite material has a core-shell structure with hollow porous SnTe / CoTe2 as the core and carbon nanofibers coated on the outer layer, and carbon materials are filled in the internal voids of the carbon nanofibers and the hollows of SnTe / CoTe2. When the double carbon-confined SnTe / CoTe2 composite material is used as the anode material of a sodium-ion battery, at a current density of 0.2 A / g, the initial capacity is not less than 697.4 mAh / g, the capacity after 50 cycles is not less than 321.5 mAh / g, the capacity retention rate is above 46.10%, and the discharge specific capacity is still 283.4 mAh / g after 200 cycles at 1 A / g, having excellent rate performance, high reversible specific capacity and long cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery energy storage technology, and more specifically to a double carbon-coated SnTe / CoTe 2 Composite material and preparation method and application thereof. Background Art

[0002] Although lithium-ion batteries have achieved great success as the main power source for portable electronic devices, hybrid electric vehicles and electric vehicles, they are limited by the shortage of lithium resources and the rising cost of raw materials, making it difficult to meet the rapid development of electric vehicles and large-scale energy storage power stations. This urgently requires the development of energy storage devices with advantages such as low cost, high energy density and long cycle life. Sodium-ion batteries have attracted widespread attention due to their abundant sodium resources, low development costs, and the same working principle as lithium-ion batteries. However, attempts to directly apply the common graphite negative electrode materials of lithium-ion batteries to sodium-ion batteries have not been successful. This is mainly due to the Na + Radius (0.102nm vs.Li + The reason is that the nanostructured carbon nanotubes (0.076 nm) are too large to be quickly and completely reversibly deintercalated between graphite layers, which results in a decrease in rate performance and reversible specific capacity. Therefore, it is necessary to develop negative electrode materials for sodium ion batteries with high specific capacity, high rate performance and long cycle life.

[0003] Metal telluride (SnTe, MoTe 2 、ZnTe、CoTe 2 、Bi 2 Te 3 and Sb 2 Te 3 etc.) are considered to be the negative electrode materials for sodium-ion batteries that are expected to achieve high rate performance and high volumetric capacity because of their advantages such as high conductivity and high density. Among them, tin telluride stands out from many metal tellurides because of its high theoretical specific capacity (626mAh / g) and abundant resources, and is expected to become the most powerful competitor among many negative electrode materials for sodium-ion batteries. However, SnTe also inherits some shortcomings of tin-based materials, such as large volume changes during sodium insertion / de-sodiumization (the volume expansion of metallic tin reaches 420% after complete sodium insertion), which causes the electrode to pulverize and fall off, resulting in rapid capacity decay, and particle agglomeration occurs during repeated dissolution and recrystallization, which further aggravates the volume effect and increases the migration distance of sodium ions. In addition, during heat treatment, due to the low melting point of Sn, Sn is often precipitated from the carbon-based composite material during the heat treatment process, causing the carbon shell to lose protection of the Sn-based active material, causing capacity decay. In addition, Sn-based materials tend to agglomerate during long-term cycling, which reduces the reaction kinetics and causes the cycling performance of sodium-ion battery negative electrode materials to decline.

[0004] In the prior art, hollow CoSn(OH) is directly synthesized by hydrothermal method. 6 The hollow porous structure is conducive to the rapid diffusion of lithium ions, and then the electrospinning method is used to synthesize one-dimensional composite nanofibers with a core-shell structure. The core-shell structure can reduce the volume change of the material during the cyclic charge and discharge process. However, due to the low melting point of Sn-based materials during heat treatment at 500-600°C, the active materials are often precipitated from the carbon matrix and agglomerated to form large-size metal particles, resulting in poor structural stability of the negative electrode material, which causes the capacity of the lithium-ion battery to decay rapidly and poor cycle stability. Summary of the invention

[0005] The present invention provides a double carbon-coated SnTe / CoTe to overcome the technical problems that the sodium ion negative electrode material provided in the prior art has low melting point Sn precipitation and agglomeration during heat treatment, the active metal particles in the prepared negative electrode material have large particle size, poor structural stability, resulting in negative electrode material capacity decay and poor cycle stability. 2 Composite materials and double carbon coating can better bind active materials, thereby better solving the common problem of Sn-based negative electrode materials that low-melting-point Sn precipitates and agglomerates, leading to capacity decay and poor cycle stability.

[0006] Another object of the present invention is to provide a double carbon-coated SnTe / CoTe 2 A method for preparing a composite material.

[0007] Another object of the present invention is to provide a double carbon-coated SnTe / CoTe 2 Application of composite materials in the preparation of negative electrode materials for sodium ion batteries.

[0008] Another object of the present invention is to provide a sodium ion battery, wherein the negative electrode of the sodium ion battery is the double carbon-coated SnTe / CoTe 2 Composite materials.

[0009] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0010] A double carbon-coated SnTe / CoTe 2 The composite material is a core-shell structure, with the core being a hollow and porous SnTe / CoTe 2 The shell is the outer layer covering the carbon nanofibers, and the internal voids of the carbon nanofibers and the SnTe / CoTe 2 The hollow part is filled with carbon material.

[0011] The double carbon-coated SnTe / CoTe of the present invention 2 Active Metal SnTe / CoTe in Composite Materials 2As the core, the outer layer is carbon nanofiber, and the internal gaps of carbon nanofiber and SnTe / CoTe 2 The hollow space is filled with carbon material. The injected polymer enters the CoSn(OH) 6 The SnTe / CoTe bond can be formed in the internal hollow structure of carbon nanofibers and between particles, and fill the pores between the core and shell of the composite material, which can fix and limit the precipitation of low-melting-point Sn from the carbon matrix during the heat treatment process, inhibit Sn from agglomerating into large-size metal particles, and form SnTe bond in the internal pores of carbon nanofibers and SnTe / CoTe bond after high-temperature tellurization. 2 The carbon material is formed in situ in the internal hollow structure and between the particles. In addition, the double carbon-coated structure can better improve the structural stability of the negative electrode material and can bind SnTe / CoTe 2 Active materials can solve the problem of Sn agglomeration in the long-term cycle of Sn-based negative electrode materials, which leads to a rapid decrease in capacity and prolongs the service life of negative electrode materials. 2 When the composite material undergoes sodium insertion / de-sodiumization process, SnTe and CoTe 2 Due to the difference in reaction potential, the volume changes of each other are suppressed, which is beneficial to reduce the stress and damage to the structure when volume strain occurs, thereby improving the cycle stability. 2 The sodium ion battery negative electrode material prepared from the composite material has high rate performance, capacity and long cycle life.

[0012] The double carbon-coated SnTe / CoTe of the present invention 2 SnTe / CoTe in composite materials 2 Particle size 19~45nm.

[0013] The double carbon-coated SnTe / CoTe of the present invention 2 Active Metal SnTe / CoTe in Composite Materials 2 When the particle size is larger than 45nm, the stress of the crystal during the sodium embedding process will increase, which may cause the structure to be destroyed, thereby reducing the cycle stability. A small particle size is beneficial to reducing stress and thus improving the cycle stability.

[0014] The double carbon-coated SnTe / CoTe of the present invention 2 The outer layer of carbon nanofiber coating in the composite material has a thickness of 60 to 80 nm.

[0015] The carbon nanofiber coating layer of the present invention has a thickness of more than 80nm, and the active material SnTe / CoTe 2 The proportion of SnTe / CoTe decreases, resulting in a decrease in the capacity of the negative electrode material, while the carbon nanofiber coating layer is less than 60nm. 2The structural stability of the composite material is reduced, resulting in a decrease in the cycle stability of the negative electrode material.

[0016] The double carbon-coated SnTe / CoTe of the present invention 2 The internal carbon filling material in the composite material accounts for the double carbon-coated SnTe / CoTe 2 2.8 to 14.5% of the mass of the composite material.

[0017] The internally filled carbon material of the present invention accounts for the double carbon-coated SnTe / CoTe 2 The mass of the composite material is greater than 14.5%, the proportion of active materials is reduced, the capacity of the negative electrode material decreases, and the internal filling carbon material accounts for the double carbon-coated SnTe / CoTe 2 The composite material mass is less than 2.8%, and there is not enough filling carbon material into SnTe / CoTe 2 In the internal hollow structure, the fixation and restriction effect on the active material is reduced, resulting in the precipitation and agglomeration of low-melting-point Sn in the negative electrode material, leading to capacity decay and poor cycle stability.

[0018] The double carbon-coated SnTe / CoTe of the present invention 2 The average pore size of the composite material is 16-24 nm.

[0019] The double carbon-coated SnTe / CoTe of the present invention 2 Active Metal SnTe / CoTe in Composite Materials 2 The mass content is 68% to 78%.

[0020] Active metal SnTe / CoTe in the composite material of the present invention 2 When the mass content is lower than 68%, the low active material content will lead to a decrease in the capacity of the negative electrode material, and the active metal SnTe / CoTe 2 When it exceeds 78%, the active material content is too high, and the filled carbon material cannot effectively restrict the active material, resulting in the precipitation and agglomeration of low-melting-point Sn in the negative electrode material, leading to capacity decay and poor cycle stability.

[0021] The present invention also protects a double carbon-coated SnTe / CoTe 2 The method for preparing the composite material comprises the following steps:

[0022] S1. The hollow CoSn(OH) 6 The particles are dispersed in an organic solvent, polyacrylonitrile is added, heated and stirred to obtain a spinning solution;

[0023] S2. electrospinning and curing the spinning solution to obtain a spinning product;

[0024] S3. The spinning product is dispersed in an organic solvent, a polymer material is added, and the mixture is stirred to obtain a mixture, 5 and the mixture is heated to 50 to 100 ℃ under vacuum conditions, and kept warm for 10 to 50h for double carbon coating;

[0025] The mass ratio of the spinning product to the polymer material in the mixed solution is 1:(1-5); the polymer material is selected from one or more of polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl alcohol and polyvinylidene fluoride.

[0026] S4. The double carbon-coated spinning product and tellurium powder are heat treated under inert gas to obtain the

[0027] Double carbon coated SnTe / CoTe 2 Composite material; the mass ratio of the double carbon-coated precursor to tellurium powder is 1:(2-4); the heat treatment temperature is 500-600°C and the time is 3-5h.

[0028] Preparation of double carbon-coated SnTe / CoTe 2 In the preparation process of the composite material, the core-shell structure of one-dimensional composite nanofibers is firstly obtained by electrospinning process, and then the polymer material is vacuum infused into the carbon nanofiber shell and CoSn(OH) 6 The gap between CoSn(OH) 6

[0029] The hollow structure inside the particles and the gaps between the particles are finally mixed with tellurium powder and heat treated under inert gas. At a high temperature of 500-600℃, the polymer material in the gaps and holes becomes a filled carbon material.

[0030] To bind SnTe / CoTe 2 Active materials, improving double carbon-coated SnTe / CoTe 2 Structural stability of composite materials.

[0031] The polymer material in S1 of the present invention is selected from one or more of polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl alcohol, and polyvinylidene fluoride. These polymer materials have good solubility in DMF / ethanol / water solvents commonly used in electrospinning, and can easily enter the carbon nanofiber shell and CoSn(OH) 6 The gap between

[0032] and CoSn(OH) 6 In the hollow structure inside the particles and in the gaps between the particles, the polymer material has good thermal stability at high temperatures and can be converted into carbon at high temperatures, thus having a fixing and limiting effect on the active substances.

[0033] Preferably, the heating temperature in S3 of the present invention is 80-90° C. and the temperature is kept at 20-30 hours.

[0034] 5. If the heating temperature in S3 of the present invention is too low, it is difficult for the polymer material to enter the spinning interior. If the temperature is too high,

[0035] The structure of the spinning product may be destroyed, resulting in a reduction in the double carbon coating effect, and the capacity and cycle performance of the negative electrode material will also decrease accordingly.

[0036] Preferably, the mass ratio of the spinning product to the polymer material in the S3 mixed solution of the present invention is 1:(2-3).

[0037] The mass ratio of the spinning product to the polymer material of the present invention is less than 1:2, and the polymer material accounts for an insufficient proportion, which reduces the double carbon coating effect and does not have sufficient filling carbon material to enter the SnTe / CoTe 2 The hollowness and pore size of the composite material will reduce the structural stability of the composite material; if the mass ratio of the spinning product to the polymer material is greater than 1:3, the polymer material accounts for too much and the carbon content of the composite material is too large, which will reduce the capacity of the negative electrode material.

[0038] The inert gas described in the present invention is argon.

[0039] The heating rate of the heat treatment process of the double carbon-coated spinning product and tellurium powder in S4 of the present invention is 2°C / min.

[0040] The curing temperature in S2 of the present invention is 200-300° C. and the curing time is 1-3 hours.

[0041] If the curing temperature of the present invention is too high, polyacrylonitrile will decompose in the air, resulting in the inability of the outer carbon nanofibers in the obtained spinning product to be uniformly coated with CoSn(OH) 6 If the curing temperature is too low, the spinning product will be difficult to be oxidized, resulting in low toughness and reduced structural stability of the spinning product, which will lead to the double carbon-coated SnTe / CoTe 2 The structural stability of the composite material decreases.

[0042] The atmosphere for the curing treatment of the present invention is an oxygen-containing atmosphere.

[0043] Preferably, polyacrylonitrile and CoSn(OH) in S1 of the present invention 6 The mass ratio is 1:(1~1.5).

[0044] Polyacrylonitrile and CoSn(OH) 6 If the mass ratio of SnTe / CoTe is less than 1:1, the carbon content will be too high, resulting in a large thickness of the carbon nanofiber coating layer. 2The proportion of the negative electrode material decreases, resulting in a decrease in the capacity of the negative electrode material, while polyacrylonitrile and CoSn(OH) 6 The mass ratio is greater than 1:1.5, the thickness of the carbon nanofiber coating layer is too thin, and the structural stability of the obtained SnTe / CoTe2 composite material is reduced, resulting in a decrease in the cycle stability of the negative electrode material.

[0045] The specific steps of electrospinning in S2 of the present invention are as follows: the spinning solution obtained in S1 is transferred to a medical syringe, and electrospinning is performed under the conditions of a voltage of 10 to 20 kV, a syringe injection speed of 1 to 3 mL / h, an inner diameter of a spinning needle of 1 to 2 mm, a distance between the needle and the receiving aluminum foil of 10 to 30 cm, and an internal temperature of the spinning device of 25 to 50 ° C.

[0046] The present invention also protects a double carbon-coated SnTe / CoTe 2 Application of composite materials in the preparation of negative electrode materials for sodium ion batteries.

[0047] The present invention also protects a sodium ion battery, wherein the negative electrode of the sodium ion battery is the double carbon-coated SnTe / CoTe 2 Composite materials.

[0048] Compared with the prior art, the present invention has the following beneficial effects:

[0049] The present invention provides a double carbon-coated SnTe / CoTe 2 The composite material is a core-shell structure, with the core being a hollow and porous SnTe / CoTe 2 The shell is the outer layer covering the carbon nanofibers, and the internal voids of the carbon nanofibers and the SnTe / CoTe 2 The hollow part of the double carbon-confined SnTe / CoTe 2 When the composite material is used as the negative electrode material of a sodium ion battery, at a current density of 0.2A / g, the first cycle capacity is not less than 697.4mAh / g, the 50-cycle capacity is not less than 321.5mAh / g, and the capacity retention rate is above 46.10%. It has excellent rate performance, high reversible specific capacity and long cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 Carbon-coated SnTe / CoTe prepared for Example 1 and Comparative Example 1 2 XRD patterns of the composite materials.

[0051] Figure 2 Double carbon-coated SnTe / CoTe prepared in Example 1 2 SEM images of the composite materials.

[0052] Figure 3Double carbon-coated SnTe / CoTe prepared in Example 1 2 TEM image of the composite material.

[0053] Figure 4 Carbon-coated SnTe / CoTe prepared in Comparative Example 1 2 SEM images of the composite materials.

[0054] Figure 5 Carbon-coated SnTe / CoTe prepared in Comparative Example 1 2 TEM image of the composite material.

[0055] Figure 6 The cycle performance diagram of the negative electrode materials prepared in Example 1 and Comparative Example 1 at 0.2 A / g.

[0056] Figure 7 The cycle performance diagram of the negative electrode materials prepared in Example 1 and Comparative Example 1 at 1.0 A / g.

[0057] Figure 8 The figure is a rate performance diagram of the negative electrode materials prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0058] The present invention will be further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Those skilled in the art will understand that the changes, replacements, and improvements made to the present invention on the basis of the present invention still belong to the protection scope of the present invention. Unless otherwise specified, the raw material reagents used in the embodiments of the present invention are conventionally purchased raw material reagents.

[0059] Source of raw materials:

[0060] Anhydrous tin tetrachloride and polyvinylidene fluoride were purchased from Guangzhou Guwei Technology Co., Ltd.; cobalt chloride and N,N-dimethylformamide were purchased from Guangzhou Shuopu Biotechnology Co., Ltd. Sodium hydroxide was purchased from Guangzhou Baijun Technology Co., Ltd.; polyacrylonitrile and polyvinyl pyrrolidone were purchased from Beijing Inokai Technology Co., Ltd.; polyvinyl alcohol was purchased from Guangzhou Lige Technology Co., Ltd.; tellurium powder was purchased from Guangzhou Rongman Biotechnology Co., Ltd.

[0061] Example 1

[0062] A double carbon-coated SnTe / CoTe 2 The composite material is a core-shell structure, with the core being a hollow and porous SnTe / CoTe 2 The shell is the outer layer covering the carbon nanofibers, and the internal voids of the carbon nanofibers and the SnTe / CoTe 2 The hollow space is filled with carbon material; SnTe / CoTe 2The particle size is 30nm, accounting for 75.6% of the composite material mass content; the outer carbon coating thickness is 60nm; the internal filling carbon material accounts for double carbon-coated SnTe / CoTe 2 9% of the composite mass; double carbon coated SnTe / CoTe 2 The average pore size of the composite material is 20nm. 2 The method for preparing the composite material comprises the following steps:

[0063] S1. CoSn(OH) 6 The hollow particles are dispersed in N,N-dimethylformamide, polyacrylonitrile is added and stirred at 80°C to obtain a spinning solution; polyacrylonitrile and CoSn(OH) 6 The mass ratio is 1:1.5;

[0064] S2. The spinning solution obtained in S1 was transferred to a medical syringe, and the voltage was 15 kV, the injection speed of the syringe was 5 degrees 2 ml / h, the inner diameter of the spinning needle was 1.5 mm, and the distance between the needle and the receiving aluminum foil was 15 cm.

[0065] Electrospinning was performed under the condition that the internal temperature of the filament device was 30° C. to obtain a spinning product; after drying for 12 hours, the spinning product was heated to 250° C. at a heating rate of 2° C. / min in an air atmosphere and kept warm for 2 hours for curing treatment to obtain a spinning product;

[0066] S3. The spinning product was dispersed in N, N-dimethylformamide, polyacrylonitrile was added, and the mixture was stirred to obtain a mixed solution of 0, wherein the mass ratio of the spinning product to polyacrylonitrile was 1:3; the mixed solution was added under vacuum

[0067] Heat to 80°C and keep warm for 20h for double carbon coating;

[0068] S4. The double carbon-coated spinning product and tellurium powder were heated to 500°C at a rate of 2°C / min in an argon atmosphere for 4 h. After natural cooling, the double carbon-coated SnTe / CoTe 2 Composite material; the mass ratio of the double carbon-coated precursor to the tellurium powder is 1:3.

[0069] 5 Example 2

[0070] A double carbon-coated SnTe / CoTe 2 The composite material is a core-shell structure, with the core being hollow and porous.

[0071] SnTe / CoTe 2 The shell is the outer layer covering the carbon nanofibers, and the internal voids of the carbon nanofibers and the SnTe / CoTe 2The hollow part is filled with carbon material; double carbon-coated SnTe / CoTe 2 Composite materials

[0072] SnTe / CoTe 2 The particle size is 25nm, accounting for 72.5% of the composite material mass content; the outer carbon coating thickness is 60nm; the inner filling carbon material accounts for double carbon coating SnTe / CoTe 2 11.7% of the composite mass; double carbon-coated SnTe / CoTe 2 The average pore size of the composite material is 18 nm.

[0073] A double carbon-coated SnTe / CoTe 2 The preparation method of the composite material comprises the steps substantially the same as those in Example 1, except that S3 is to disperse the spinning product in N,N-dimethylformamide, add polyethylene

[0074] Pyrrolidone, stirring evenly to obtain a mixed solution, wherein the mass ratio of the spinning product to polyvinyl pyrrolidone in the mixed solution is 51:4; heating the mixed solution to 90°C under vacuum conditions, keeping the temperature for 10 hours, and performing double carbon coating.

[0075] Example 3

[0076] A double carbon-coated SnTe / CoTe 2 The composite material is a core-shell structure, with the core being hollow and porous.

[0077] SnTe / CoTe 2 The shell is the outer layer covering the carbon nanofibers, and the internal voids of the carbon nanofibers and the SnTe / CoTe 2 The hollow part is filled with carbon material; double carbon-coated SnTe / CoTe 2 SnTe / CoTe in composite materials 2 The particle size is 20nm, accounting for 70.2% of the composite material mass content; the outer carbon coating thickness is 60nm; the internal filling carbon material accounts for double carbon-coated SnTe / CoTe 2 14.5% of the composite mass; double carbon-coated SnTe / CoTe 2 The average pore size of the composite material is 17 nm.

[0078] A double carbon-coated SnTe / CoTe 2 The preparation method of the composite material comprises the steps basically the same as those in Example 1, the difference being that in S3, the spinning product is dispersed in N,N-dimethylformamide, polyvinyl alcohol is added, and the mixture is stirred evenly to obtain a mixed solution, wherein the mass ratio of the spinning product to the polyvinyl alcohol in the mixed solution is 1:5; the mixed solution is heated to 60°C under vacuum conditions, kept warm for 25 hours, and double carbon coated.

[0079] Example 4

[0080] A double carbon-coated SnTe / CoTe 2 The composite material is a core-shell structure, with the core being a hollow and porous SnTe / CoTe 2 The shell is the outer layer covering the carbon nanofibers, and the internal voids of the carbon nanofibers and the SnTe / CoTe 2 The hollow part is filled with carbon material; double carbon-coated SnTe / CoTe 2 SnTe / CoTe in composite materials 2 The particle size is 45nm, accounting for 77.9% of the composite material mass content; the outer carbon coating thickness is 60nm; the internal filling carbon material accounts for double carbon-coated SnTe / CoTe 2 5.8% of the composite mass; double carbon-coated SnTe / CoTe 2 The average pore size of the composite material is 24 nm.

[0081] A double carbon-coated SnTe / CoTe 2 A method for preparing a composite material comprises steps substantially the same as those of Example 1, the difference being that in S3, the spinning product is dispersed in N,N-dimethylformamide, polyvinylidene fluoride is added, and the mixture is stirred evenly to obtain a mixed solution, wherein the mass ratio of the spinning product to polyvinylidene fluoride in the mixed solution is 1:2; the mixed solution is heated to 50°C under vacuum conditions, kept warm for 35 hours, and double carbon coated.

[0082] Example 5

[0083] A double carbon-coated SnTe / CoTe 2 The composite material is a core-shell structure, with the core being a hollow and porous SnTe / CoTe 2 The shell is the outer layer covering the carbon nanofibers, and the internal voids of the carbon nanofibers and the SnTe / CoTe 2 The hollow part is filled with carbon material; double carbon-coated SnTe / CoTe 2 SnTe / CoTe in composite materials 2 The particle size is 19nm, accounting for 68.8% of the composite material mass content; the outer carbon coating thickness is 80nm; the internal filling carbon material accounts for double carbon-coated SnTe / CoTe 2 2.8% of the composite mass; double carbon-coated SnTe / CoTe 2 The average pore size of the composite material is 16 nm.

[0084] A double carbon-coated SnTe / CoTe 2The preparation method of the composite material comprises the same steps as those in Example 1, except that: the polyacrylonitrile and CoSn(OH) in S1 are 6 The mass ratio is 1:1; S3 is to disperse the spinning product in N,N-dimethylformamide, add polyacrylonitrile, and stir evenly to obtain a mixed solution, in which the mass ratio of the spinning product to polyacrylonitrile is 1:1; the mixed solution is heated to 60°C under vacuum conditions and kept warm for 45 hours for double carbon coating.

[0085] Example 6

[0086] A double carbon-coated SnTe / CoTe 2 The composite material is a core-shell structure, with the core being a hollow and porous SnTe / CoTe 2 The shell is the outer layer covering the carbon nanofibers, and the internal voids of the carbon nanofibers and the SnTe / CoTe 2 The hollow part is filled with carbon material; double carbon-coated SnTe / CoTe 2 SnTe / CoTe in composite materials 2 The particle size is 20nm, accounting for 70.8% of the composite material mass content; the outer carbon coating thickness is 80nm; the internal filling carbon material accounts for double carbon-coated SnTe / CoTe 2 7.5% of the composite mass; double carbon coated SnTe / CoTe 2 The average pore size of the composite material is 17 nm.

[0087] A double carbon-coated SnTe / CoTe 2 The preparation method of the composite material comprises the same steps as those in Example 1, except that: the polyacrylonitrile and CoSn(OH) in S1 are 6 The mass ratio is 1:1; S3 is to disperse the spinning product in N,N-dimethylformamide, add polyacrylonitrile, and stir evenly to obtain a mixed solution, in which the mass ratio of the spinning product to polyacrylonitrile is 1:2.5; the mixed solution is heated to 100°C under vacuum conditions and kept warm for 50 hours for double carbon coating.

[0088] Examples 1 to 6 Preparation of double carbon-coated SnTe / CoTe 2 The specific parameters of the composite materials are shown in Table 1.

[0089] Table 1 Preparation of double carbon-coated SnTe / CoTe in Examples 1 to 6 2 Composite material parameters

[0090]

[0091] Comparative Example 1

[0092] A carbon-coated SnTe / CoTe 2The composite material is a core-shell structure, with the core being a hollow and porous SnTe / CoTe 2 , the shell is the outer layer coated with carbon nanofibers; double carbon coated SnTe / CoTe 2 SnTe / CoTe in composite materials 2 The particle size is 100nm, accounting for 88.4% of the composite material mass content; the outer carbon coating thickness is 60nm; the internal filling carbon material accounts for 88.4% of the carbon-coated SnTe / CoTe 2 0% of composite mass; double carbon coated SnTe / CoTe 2 The average pore size of the composite material is 30 nm.

[0093] A double carbon-coated SnTe / CoTe 2 The method for preparing the composite material comprises steps substantially the same as those in Example 1, except that there is no step S3.

[0094] Performance Testing

[0095] Carbon-coated SnTe / CoTe was prepared from Examples 1 to 6 and Comparative Example 1. 2 The composite materials were characterized by morphology and tested for electrical properties.

[0096] Crystal structure and morphology characterization

[0097] Figure 1 Carbon-coated SnTe / CoTe prepared for Example 1 and Comparative Example 1 2 XRD patterns of composite materials, including SnTe / CoTe 2 @DC is the composite material prepared in Example 1, SnTe / CoTe 2 @C is the composite material obtained in Example 1. Figure 1 It can be seen that all diffraction peaks are related to SnTe and CoTe 2 The standard card is consistent with that of SnTe / CoTe 2 The crystals were successfully synthesized. It is worth noting that no double carbon-coated SnTe / CoTe 2 The diffraction peak intensity of SnTe is strong and the half-peak width is narrow, indicating that SnTe has strong crystallinity and large particles, which means that SnTe agglomerates inside the spun fiber to form large particles.

[0098] Figure 2 and Figure 3 Double carbon-coated SnTe / CoTe prepared in Example 1 2 SEM and TEM images of the composite material. Figure 4 and Figure 5 Carbon-coated SnTe / CoTe prepared in Comparative Example 1 2The SEM and TEM images of the composite material show that the SnTe / CoTe composite material in Comparative Example 1 is not double-carbon coated. 2 The composite material will precipitate from the spinning product during high temperature heat treatment. 2 The composite material will agglomerate internally during high temperature heat treatment, making it difficult to maintain hollow pores. 2 The composite material can still maintain the hollow porous shape of the cubic block inside the spinning product, and no Sn particles are precipitated, and the composite material has a stable structure.

[0099] Carbon-coated SnTe / CoTe was prepared for Examples 1 to 6. 2 The composite material was tested by thermogravimetric analysis in the temperature range of room temperature to 700°C, and the mass content of the internal filling carbon material in the composite material was tested in air atmosphere. 2 SnTe / CoTe in composite materials 2 The particle size and the outer carbon coating thickness were measured. Carbon-coated SnTe / CoTe composite materials of Examples 1 to 6 and Comparative Example 1 were prepared by BET. 2 The average pore size of the composite material was tested. The test results of the composite materials prepared in Examples 1 to 6 and Comparative Example 1 are shown in Table 2.

[0100] Table 2 Double carbon-coated SnTe / CoTe prepared in Examples 1 to 6 and Comparative Example 1 2 Composite material characteristics

[0101]

[0102]

[0103] Electrical performance test

[0104] The carbon-coated SnTe / CoTe prepared in Examples 1 to 6 and Comparative Example 1 was 2 The composite material was made into negative electrode material and the electrical performance was tested. The test results are shown in Figure 6 , Figure 7 , Figure 8 and Table 3.

[0105] Figure 6 The cycle performance diagram of the negative electrode material obtained in Example 1 and Comparative Example 1 at 0.2A / g, where SnTe / CoTe 2 @DC is the composite material prepared in Example 1, SnTe / CoTe 2@C is the composite material prepared in Example 1. Double carbon-coated SnTe / CoTe 2 After 50 cycles at a current density of 0.2 A / g, the capacity can still be maintained at 385.7 mAh / g, while SnTe / CoTe without the second step of carbon coating treatment 2 Under the same conditions, it is only 229.9 mAh / g. Figure 7 The cycle performance diagram of the negative electrode material obtained in Example 1 and Comparative Example 1 at 1.0 A / g, where SnTe / CoTe 2 @DC is the composite material prepared in Example 1, SnTe / CoTe 2 @C is the composite material prepared in Example 1. Double carbon-coated SnTe / CoTe 2 The discharge capacity of SnTe / CoTe without the second step of carbon coating is still 283.4 mAh / g after 200 cycles at 1 A / g. 2 Under the same conditions, it is only 202.8 mAh / g. The results show that the double carbon coating can well protect the hollow structure of the metal active material inside the spinning product, thereby improving the cycle stability. And further illustrate the well-designed SnTe / CoTe 2 The ultra-high rate performance indicates that the double carbon coating can extremely well protect the hollow structure of the metal active substances inside the spinning product, thereby improving the cycle stability.

[0106] Figure 8 The rate performance diagram of the negative electrode material provided in Example 1 and Comparative Example 1, wherein SnTe / CoTe 2 @DC is the composite material prepared in Example 1, SnTe / CoTe 2 @C is the composite material obtained in Example 1. Example 1 is double-carbon coated. Under the protection of internal and external double carbon, its stability is well improved. In addition, due to the high conductivity of tellurium and SnTe / CoTe 2 The better ion / electron transfer rate brought by the heterojunction makes it have better rate performance. In contrast, the comparative example 1 lacks internal carbon protection, so that it will agglomerate internally during high-temperature heat treatment, and tin will also precipitate out of the carbon fiber at high temperature, which will reduce the cycle stability. When the rate performance test is carried out, the capacity decays rapidly, which reduces the rate performance.

[0107] Table 3 Performance test of negative electrode materials prepared in Examples 1 to 6 and Comparative Example 1

[0108] First cycle capacity mAh / g 50 cycle capacity mAh / g Capacity retention rate % Example 1 731.0 385.7 52.76% Example 2 712.1 332.4 46.68% Example 3 697.4 321.5 46.10% Example 4 739.3 358.5 48.49% Example 5 742.6 350.4 47.19% Example 6 728.5 365.6 50.19% Comparative Example 1 743.6 229.9 30.91%

[0109] Note: The test conditions for the first cycle capacity and the capacity after 50 cycles of the negative electrode materials in Table 1 are both at a current density of 0.2A / g.

[0110] Comparing the data in Table 2 and Table 3, it can be seen that the double carbon-coated SnTe / CoTe prepared in Examples 1 to 6 2 SnTe / CoTe in composite materials 2 The particle size is 19-45nm, the mass content is 68%-78%; the outer layer of carbon nanofiber coating thickness is 60-80nm; the internal filling carbon material accounts for double carbon coating SnTe / CoTe 2 2.8-14.5% of the composite material mass, double carbon coated SnTe / CoTe 2 The average pore size of the composite material is 16-24 nm. 2 The composite material is used as the negative electrode material of the sodium ion battery. At a current density of 0.2A / g, the first cycle capacity is not less than 697.4mAh / g, and the maximum can reach 742.6mAh / g. The 50-cycle capacity is not less than 321.5mAh / g, and the capacity retention rate is above 46.10%, and the maximum can reach 52.76%. 2 SnTe / CoTe in composite materials 2 The particle size is 55nm, the mass content is 88.4%; the outer layer of carbon nanofiber coating thickness is 60nm, and the carbon-coated SnTe / CoTe 2 The average pore size of the composite material is 30nm, and the absence of carbon filling material has a significant impact on the SnTe / CoTe 2 Therefore, although the first cycle capacity of the composite material obtained in comparative example 1 is 743.6 mAh / g, which is not much different from the first cycle capacity of example 5, its 50 cycle capacity quickly drops to 229.9 mAh / g, and the capacity retention rate is only 30.91%. 2 The composite material has high capacity and excellent cycle stability as anode material for sodium ion batteries.

[0111] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A double carbon-coated SnTe / CoTe2 composite material, characterized in that: The double carbon-coated SnTe / CoTe2 composite material has a core-shell structure, wherein the core is hollow and porous SnTe / CoTe2, the shell is an outer layer of coated carbon nanofibers, and the internal voids of the carbon nanofibers and the hollow core of the SnTe / CoTe2 are filled with carbon material; wherein the internally filled carbon material accounts for 2.8 to 14.5% of the mass of the double carbon-coated SnTe / CoTe2 composite material.

2. The double carbon-coated SnTe / CoTe2 composite material according to claim 1, characterized in that: The SnTe / CoTe2 particle size is 19 to 45 nm.

3. The double carbon-coated SnTe / CoTe2 composite material according to claim 1, characterized in that: The outer layer of carbon nanofiber coating has a coating thickness of 60 to 80 nm.

4. The double carbon-coated SnTe / CoTe2 composite material according to claim 1, characterized in that: The average pore size of the double carbon-coated SnTe / CoTe2 composite material is 16-24 nm.

5. The double carbon-coated SnTe / CoTe2 composite material according to claim 1, characterized in that: The mass content of active metal SnTe / CoTe2 in the double carbon-coated SnTe / CoTe2 composite material is 68% to 78%.

6. A method for preparing the double carbon-coated SnTe / CoTe2 composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. The hollow CoSn(OH)6 particles are dispersed in an organic solvent, polyacrylonitrile is added, heated and stirred to obtain a spinning solution; S2. electrospinning and curing the spinning solution to obtain a spinning product; S3. The spinning product is dispersed in an organic solvent, a polymer material is added, and the mixture is stirred to obtain a mixed solution, and the mixed solution is heated to 50 to 100° C. under vacuum conditions, and kept warm for 10 to 50 hours to perform double carbon coating; the mass ratio of the spinning product to the polymer material in the mixed solution is 1:(1 to 5); S4. The double carbon-coated spinning product and tellurium powder are heat treated under an inert gas to obtain the double carbon-coated SnTe / CoTe2 composite material; The mass ratio of the double carbon-coated spinning product to tellurium powder is 1:(2-4); the heat treatment temperature is 500-600°C, and the time is 3-5h; the mass ratio of polyacrylonitrile to CoSn(OH)6 in S1 is 1:(1-1.5); the curing temperature in S2 is 200-300°C.

7. Use of the double carbon-coated SnTe / CoTe2 composite material according to any one of claims 1 to 5 in preparing a negative electrode material for a sodium ion battery.

8. A sodium ion battery, characterized in that: The negative electrode of the sodium ion battery is the double carbon-coated SnTe / CoTe2 composite material according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Nanostructured materials for battery applications

    CN102428763A

  • Cobalt ditelluride / carbon nanofiber material and preparation method and application thereof

    CN112886007A